Open/distance learning and the changing labour market: Toward a framework for rethinking educational governance structures - Largoza, Gerardo L. (Animo Repository, 2003)
The progressive liberalisation of the Philippine economy has produced a domestic labour market characterised by increasing contractualisation and diminished security of tenure. Re-taining and continuing education have been suggested as the basis for a viable safety net system. We argue that while distance learning holds promise as a means of maintaining Filipino competitiveness, its administration must be rationalised and implemented within the context of more wide-ranging reforms within the education sector. In addition, open and distance learning may, in fact, facilitate the reform process itself, particularly in the areas of improving teaching competence, increasing the preparedness of students for higher education, establishing a more uniform accreditation system, as well as updating and harmonising standards for professional services.